Large Animal Models of Breast Cancer - Mondal, Pinaki; Bailey, Katie L.; Cartwright, Sara B.; Band, Vimla; Carlson, Mark A. (Frontiers in Oncology, 2022)
In this mini review the status, advantages, and disadvantages of large animal modeling of breast cancer (BC) will be discussed. While most older studies of large animal BC models utilized canine and feline subjects, more recently there has been interest in development of porcine BC models, with some early promising results for modeling human disease. Widely-used rodent models of BC were briefly reviewed to give context to the work on the large animal BC models. Availability of large animal BC models could provide additional tools for BC research, including availability of human-sized subjects and BC models with greater biologic relevance.